Absolute phase unwrapping with SVM for fringe‐projection profilometry. Issue 12 (1st October 2020) - Xiang, Sen; Deng, Huiping; Wu, Jin; Zhu, Changjian
Abstract : Phase unwrapping is a fundamental task in phase‐based profilometry. Existing spatial and temporal approaches are facing challenges such as error propagation and low efficiency. In this study, the authors propose a learning‐based method that uses a support vector machine (SVM) to perform phase unwrapping, where the problem is solved as a classification task. To be specific, seven elements, extracted from the captured patterns and the wrapped phase, form the input feature vector and the fringe order is the output class. Besides, a radial basis function kernel SVM is adopted as the model. The proposed method is conducted independently for every pixel, and does not suffer from error propagation in the spatial unwrapping. Moreover, it needs fewer patterns than temporal unwrapping since only one phase map is required. Simulation and experimental results demonstrate that the proposed scheme produces precise depth maps, which are comparable with the complex quality‐guided methods but at a much faster speed.